1984
DOI: 10.1139/l84-067
|View full text |Cite
|
Sign up to set email alerts
|

Initial operating experiences of a nutrient removal process (Modified Bardenpho) at Kelowna, British Columbia

Abstract: A new wastewater treatment plant that utilizes the “Modified Bardenpho” process for nutrient removal has recently been commissioned in Kelowna, B.C. The 260 L/s facility (130 L/s in each of two parallel modules) has been operating at full design flow through one module for over 6 months.Two months of operating time was required to establish the nitrification–denitrification capabilities and to build up the phosphorus release–uptake mechanism in the biomass. Subsequent to that start-up period, the process has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…This WWTP was the first (the current configuration opened in 1983) in North America specifically designed to include a sequence of anaerobic, anoxic, and aerobic environments for the removal of carbon, nitrogen, and phosphorus (Oldham and Stevens 1984); the authors of a previous report claimed the honor for Palmetto, Florida, in 1989 (Zitomer and Speece 1993).At present, the Kelowna wastewater system serves 1050 institutional users and an estimated population of ∼70 000 (City of Kelowna 2003) with 28 pumping stations, >400 km of sewage pipe, and a 10 ha WWTP capable of treating 40 ML/d. 2 and 3 for plant schematics).…”
Section: Introductionmentioning
confidence: 99%
“…This WWTP was the first (the current configuration opened in 1983) in North America specifically designed to include a sequence of anaerobic, anoxic, and aerobic environments for the removal of carbon, nitrogen, and phosphorus (Oldham and Stevens 1984); the authors of a previous report claimed the honor for Palmetto, Florida, in 1989 (Zitomer and Speece 1993).At present, the Kelowna wastewater system serves 1050 institutional users and an estimated population of ∼70 000 (City of Kelowna 2003) with 28 pumping stations, >400 km of sewage pipe, and a 10 ha WWTP capable of treating 40 ML/d. 2 and 3 for plant schematics).…”
Section: Introductionmentioning
confidence: 99%
“…In the basic Bardenpho plant, they passed the RAS through an anoxic zone and then through an anaerobic stage with a portion of the RAS being fermented and returned to the anaerobic zone. P may also be released through endogenous respiration (Oldham & Stevens, 1984) when the uptake is completed in a plug-flow aeration zone some distance before the end of the aerobic zone of the basin. Vollertsen et al (2005) fermented 10-15% of the RAS before returning it to the anaerobic zone and this assisted in P removal in more than 40 Danish treatment plants.…”
Section: Fermentation Of Mlss or Rasmentioning
confidence: 99%
“…This has taken shape largely through the introduction of sewage wastes that were observed to have highly soluble COD or low molecular weight volatile fatty acids (VFA), particularly acetic and propionic forms. Where plants did not have sufficient VFA in the incoming wastewater, diversion of supernatant from gravity solids thickeners, and later the development of side stream fermenters/thickeners was shown to provide a needed VFA supplement (Oldham, 1984), which led to advancement in fermenter design. Optimization studies showed continued benefit in enhancement of the nutrient removal process.…”
Section: Fermentation Technology For Ebnrmentioning
confidence: 99%
“…With the exception of a few researchers (Rabinowitz (1985) and Elefsiniotis (1994Elefsiniotis ( , 2004), the development of the fermenters has also largely overlooked the large body of knowledge of acid digesters from Ghosh (1974Ghosh ( , 1975Ghosh ( , 1987Ghosh ( , 1995Ghosh ( , 1997Ghosh ( , and 2003 in favour of hydraulic residence time (HRT) controlled sidestream thickeners and completely mixed stirred tank (CMST) reactors. The development of the current fermenter design appears to have been partly in response to the EBNR researchers such as Lötter (1992), who recognized VFA to be an important substrate for the EBNR process, and the related earlier discovery that gravity thickeners could supply this source when used appropriately, (Oldham (1984), Barnhard (1994)). …”
Section: Introductionmentioning
confidence: 99%